A ligand-based comparative molecular field analysis (CoMFA) and homology model based molecular docking studies on 3′, 4′-dihydroxyflavones as rat 5-lipoxygenase inhibitors: Design of new inhibitors. (December 2017) - Ahamed, T.K.Shameera; Muraleedharan, K.
Graphical abstract: Highlights: Developed a CoMFA model based on the class of 3′, 4′-dihydroxyflavone derivatives. Constructed a homology model for rat 5-LOX. Ligand-receptor interactions are characterized through molecular docking study. Docking results coincide well with the CoMFA analysis. Five potential rat 5-LOX inhibitors with good predicted activities were designed. Abstract: In this study, ligand based comparative molecular field analysis (CoMFA) with five principal components was performed on class of 3′, 4′-dihydroxyflavone derivatives for potent rat 5-LOX inhibitors. The percentage contributions in building of CoMFA model were 91.36% for steric field and 8.6% for electrostatic field. R 2 values for training and test sets were found to be 0.9320 and 0.8259, respectively. In case of LOO, LTO and LMO cross validation test, q 2 values were 0.6587, 0.6479 and 0.5547, respectively. These results indicate that the model has high statistical reliability and good predictive power. The extracted contour maps were used to identify the important regions where the modification was necessary to design a new molecule with improved activity. The study has developed a homology model for rat 5-LOX and recognized the key residues at the binding site. Docking of most active molecule to the binding site of 5-LOX confirmed the stability and rationality of CoMFA model. Based on molecular docking results and CoMFA contour plots, new inhibitors with higher activity with respect to the most active compound in data set were designed.